Comparison between traditional wireless vehicular networks and fog computing-based wireless vehicular networks. - ghanem, duaa (Latakia University Journal -Engineering Sciences Series, 2025)
With the advancement of technology and the growth of the number of smart cars, traditional VANETs face a number of technical difficulties due to lack of scalability and flexibility, and insufficient communication intelligence when deploying and managing them. Therefore, fog computing plays an important role in obtaining optimal solutions to the problems found in VANETs. Therefore, because of the importance of using fog computing in wireless vehicular ad hoc networks (VANETs), and due to the lack of research in the field of evaluating the performance of wireless ad hoc vehicular networks based on VANET based Fog Computing, in this research we studied the importance of using fog computing in the wireless vehicular ad hoc network environment, where a comparison was made. Between traditional wireless vehicular networks and wireless vehicular networks based on fog computing using the NS2.35 simulator in terms of a set of evaluation parameters, which are throughput, end-to-end delay, packet delivery rate, and the number of lost packets in the network, in order to know the features and positive effects that have been benefited from, and to know the impact of using Fog computing in wireless vehicular networks in terms of routing emergency messages, alleviating congestion, and sending data in real time. The use of fog computing in wireless vehicular networks has had an important impact in terms of reducing end-to-end delay and increasing productivity and packet delivery rate compared to traditional wireless vehicular networks.